Transforming growth factor β1 and interleukin 4 induced α smooth muscle actin expression and myofibroblast-like differentiation in human synovial fibroblasts in vitro: modulation by basic fibroblast growth factor. Issue 7 (1st July 1997) - Mattey, D L; Dawes, P T; Nixon, N B; Slater, H
Abstract : OBJECTIVE: To discover if α smooth muscle actin expression and myofibroblastic differentiation are induced in synovial fibroblasts by cytokines found in the inflamed RA joint. METHODS: Immunofluorescent microscopy and western blotting were used to examine different cultures of human synovial fibroblasts for expression of α actin in the presence of the cytokines transforming growth factor β (TGFβ1), interleukin 1α (IL1α), IL4, IL6, tumour necrosis factor α (TNFα), and basic fibroblast growth factor (FGF). RESULTS: A small but significant population of cells (14.4 ± 12.9%) expressed α actin under standard culture conditions. Upon treatment with TGFβ1 there was a pronounced increase in the number of cells expressing α actin (68.1 ± 5.49%), accompanied by a change in morphology to a myofibroblast-like phenotype. Other cytokines found within the inflamed joint such as IL1, TNFα, IL6, and basic FGF failed to induce α actin expression. However, IL4, which is normally absent or only present at low concentrations in the RA joint had a similar effect to TGFβ1. It was also found that basic FGF inhibited the induction of α actin expression by TGFβ1 and IL4. CONCLUSION: In the presence of TGFβ1 or IL4, fibroblasts derived from synovial tissue or synovial fluid are induced to differentiate into myofibroblast-like cells containing the α smooth muscle form of actin. This differentiation is inhibited by basic FGF. It is suggested that the balance between these particular cytokines may be important in the modulation of fibroblast behaviour, which could have significant effects on joint repair mechanisms and the generation of fibrous tissue within the rheumatoid joint.